Grid artifact reduction for direct digital radiography detectors based on rotated stationary grids with homomorphic filtering. Issue 6 (23rd May 2013) - Kim, Dong Sik; Lee, Sanggyun
Abstract : Purpose: Grid artifacts are caused when using the antiscatter grid in obtaining digital x‐ray images. In this paper, research on grid artifact reduction techniques is conducted especially for the direct detectors, which are based on amorphous selenium. Methods: In order to analyze and reduce the grid artifacts, the authors consider a multiplicative grid image model and propose a homomorphic filtering technique. For minimal damage due to filters, which are used to suppress the grid artifacts, rotated grids with respect to the sampling direction are employed, and min‐max optimization problems for searching optimal grid frequencies and angles for given sampling frequencies are established. The authors then propose algorithms for the grid artifact reduction based on the band‐stop filters as well as low‐pass filters. Results: The proposed algorithms are experimentally tested for digital x‐ray images, which are obtained from direct detectors with the rotated grids, and are compared with other algorithms. It is shown that the proposed algorithms can successfully reduce the grid artifacts for direct detectors. Conclusions: By employing the homomorphic filtering technique, the authors can considerably suppress the strong grid artifacts with relatively narrow‐bandwidth filters compared to the normal filtering case. Using rotated grids also significantly reduces the ringing artifact. Furthermore, for specific grid frequencies and angles, the authors can use simple homomorphic low‐pass filters in the spatial domain, and thus alleviate the grid artifacts with very low implementation complexity.